DataSheet_1_Nordic Blue Carbon Ecosystems: Status and Outlook.pdf - Dorte Krause-Jensen; Hege Gundersen; Mats Björk; Martin Gullström; Martin Dahl; Maria E. Asplund; Christoffer Boström; Marianne Holmer; Gary T. Banta; Anna Elizabeth Løvgren Graversen; Morten Foldager Pedersen; Trine Bekkby; et al. (2022)
Vegetated coastal and marine habitats in the Nordic region include salt marshes, eelgrass meadows and, in particular, brown macroalgae (kelp forests and rockweed beds). Such habitats contribute to storage of organic carbon (Blue Carbon – BC) and support coastal protection, biodiversity and water quality. Protection and restoration of these habitats therefore have the potential to deliver climate change mitigation and co-benefits. Here we present the existing knowledge on Nordic BC habitats in terms of habitat area, C-stocks and sequestration rates, co-benefits, policies and management status to inspire a coherent Nordic BC roadmap. The area extent of BC habitats in the region is incompletely assessed, but available information sums up to 1,440 km 2 salt marshes, 1,861 (potentially 2,735) km 2 seagrass meadows, and 16,532 km 2 (potentially 130,735 km 2 , including coarse Greenland estimates) brown macroalgae, yielding a total of 19,833 (potentially 134,910) km 2 . Saltmarshes and seagrass meadows have experienced major declines over the past century, while macroalgal trends are more diverse. Based on limited salt marsh data, sediment C-stocks average 3,311 g C org m -2 (top 40-100 cm) and sequestration rates average 142 g C org m -2 yr -1 . Eelgrass C-stocks average 2,414 g C org m -2 (top 25 cm) and initial data for sequestration rates range 5-33 g C org m -2 , quantified for one Greenland site and one short term restoration. For Nordic brown macroalgae, peer-reviewed estimates of sediment C-stock and sequestration are lacking. Overall, the review reveals substantial Nordic BC-stocks, but highlights that evidence is still insufficient to provide a robust estimate of all Nordic BC-stocks and sequestration rates. Needed are better quantification of habitat area, C-stocks and fluxes, particularly for macroalgae, as well as identification of target areas for BC management. The review also points to directives and regulations protecting Nordic marine vegetation, and local restoration initiatives with potential to ...